Pengaruh Kempotensi, Kepemimpinan, Motivasi dan Tanggung Jawab Terhadap Kinerja Pegawai Pada Puskesmas Banggai Kecamatan Banggai Kabupaten Banggai Laut - Zaitun, Cakra; Jannah, Miftahul; Muzfah, Wardah (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
In facing the development of health services, especially to expand the reach and improve the quality of services to the community. Various types and levels of appropriate professional health are needed in the application of advances in science and technology and through the application of moral and ethical values. An important issue in terms of current reform is that the centralized system that has been practiced so far has proven unable to answer the problems that exist in society. Then the low performance of services has become a kind of bad image attached to the health sector. Many efforts have been made in that direction, but the results have not been adequate. Especially in terms of potential, leadership, motivation and responsibility. An important issue in terms of current reform is that the centralized system that has been practiced so far has proven unable to answer the problems that exist in society. Then the low performance of services has become a kind of bad image attached to the health sector. Many efforts have been made in that direction, but the results have not been adequate. The purpose of this study is to determine the effect of competence, leadership, motivation and responsibility on outpatient health services for Banggai Health Center employees. To determine the dominant factors that influence outpatient health services for Banggai Health Center employees, the method in this study is Descriptive analysis, The conclusion in this study is that Competence, Leadership, motivation and responsibility are factors that significantly influence the Performance of Banggai Health Center Employees.